Choice of action for victims of cyber gender-based violence (sexting) via WhatsApp - Lestari, Shania Putri; Mutmainnah (C-DISC, 2023)
This research is motivated by the development of information and communication technology, amid the widespread Internet network and the popular use of social media. This condition has increased the intensity of people's use of social media, one of which is WhatsApp. The use of WhatsApp not only brings positive value, but also has the potential to become a space for acts of harassment, which has an impact on the rise of cyber gender-based violence, one of which is sexting. The purpose of this study is to find out about the cyber gender-based violence (sexting) that occurs through WhatsApp in the campus environment. In particular, it aims to find out the victim's choice of action against the perpetrator in the case of cyber gender-based violence (sexting) via WhatsApp. The study uses a qualitative research method with a phenomenological approach. Supported by George Herbert Blumer's theory of symbolic interactionism, the results of this study show that sexting occurs in verbal and nonverbal forms. The perpetrators of sexting come from inside and outside the campus, with the status of the closest person to a stranger. The victim's actions toward the perpetrator are divided into three types of actions, namely, reporting, not reporting, and fighting back against the perpetrator. The action of not reporting is divided into four types of actions, namely, reprimanding, redirecting the conversation, blocking, and rejecting the perpetrator's call.